Discrepancy Between Clinician- and Patient-Reported Definitions of Mild Degenerative Cervical Myelopathy and Surgical Outcomes - Takahiro Kitagawa; Narihito Nagoshi; Junichi Yamane; Toshiki Okubo; Reo Shibata; Yoshiomi Kobayashi; Kanehiro Fujiyoshi; Yoshiyuki Yato; Tatsuya Yamamoto; Kazuya Kitamura; Takeshi Ikegami; Takahito Iga; et al. (Global Spine Journal, 2026)
Study Design Prospective multicenter observational cohort study. Objective To redefine mild degenerative cervical myelopathy (DCM) using a patient-reported severity framework derived from Japanese Orthopaedic Association Cervical Myelopathy Evaluation Questionnaire (JOACMEQ) and to compare surgical outcomes with the conventional clinician-reported definition. Methods Patients with DCM undergoing surgery at 10 spine centers were enrolled. Mild DCM was defined using two criteria: a clinician-reported definition based on Japanese Orthopaedic Association (JOA) score (≧ 14.5) and a patient-reported definition derived from principal component analysis of JOACMEQ domains and Numerical Rating Scale (NRS) pain scores. Patients were categorized into four groups: Dual-Mild, Clinician-Mild, Patient-Mild, and Non-Mild. Postoperative outcomes were assessed using achievement of minimum clinically important difference (MCID) for JOA score, JOACMEQ, NRS, and Short Form-36 (SF-36). Multivariable logistic regression models were used to estimate adjusted probabilities of MCID achievement. Results Among 930 eligible patients, 122 met criteria for mild DCM by each definition. Patients classified as Patient-Mild demonstrated higher baseline function and lower pain scores but showed significantly lower adjusted probabilities of achieving MCID in pain-related outcomes and SF-36 physical component summary (PCS) (odds ratio for PCS, 0.346 [0.196-0.589]; p < 0.001). In contrast, Clinician-Mild status was associated with sustained postoperative improvement. Conclusion Definitions of mild DCM differ substantially between clinician- and patient-reported criteria. Patients who perceive their disease as mild exhibit limited postoperative improvement. Incorporating patient-reported severity into preoperative assessment may better inform expectations and shared decision-making regarding surgery in mild DCM.